Effects of the insecticide imidacloprid on aquatic invertebrate communities of the Ecuadorian Amazon - Cabrera, Marcela (2024)
Imidacloprid is a neonicotinoid insecticide that has received particular attention due to its widespread use and potential adverse effects for aquatic and terrestrial ecosystems. Its toxicity to aquatic organisms has been evaluated in central and southern Europe as well as in (sub-)tropical regions of Africa and Asia, showing high toxic potential for some aquatic insects and zooplankton taxa. However, its toxicity to aquatic organisms representative of tropical regions of Latin America has never been evaluated. To fill this knowledge gap, we carried out a mesocosm experiment to assess the short- and long-term effects of imidacloprid on freshwater invertebrate communities representative of the Ecuadorian Amazon. A mesocosm experiment was conducted with five weekly applications of imidacloprid at four nominal concentrations (0.01 μg/L, 0.1 μg/L, 1 μg/L and 10 μg/L). Toxic effects were evaluated on zooplankton and macroinvertebrate populations and communities, as well as on water quality parameters for 70 days. Given the climatic conditions prevailing in the study area, characterized by a high solar radiation and abundant rainfall that resulted in mesocosm overflow, there was a rapid dissipation of the test compound from the water column (half-life: 4 days). The macroinvertebrate taxa Callibaetis pictus (Ephemeroptera), Chironomus sp. (Diptera), and the zooplankton taxon Macrocyclops sp., showed population declines caused by the imidacloprid treatment, with a 21-d Time Weighted Average No Observed Effect Concentrations (21-d TWA NOEC) of 0.46 μg/L, except for C. pictus which presented a 21-d TWA NOEC of 0.05 μg/L. In general terms, the sensitivity of these taxa to imidacloprid was greater than that reported for surrogate taxa in temperate zones and similar to that reported in other (sub-)tropical regions. These results confirm the high sensitivity of tropical aquatic invertebrates to this compound and suggest the need to establish regulations for the control of imidacloprid contamination in Amazonian freshwater ecosystems.